Experiences of self‐management among young adults with Type 1 diabetes in the context of a structured education programme: a qualitative study. Issue 11 (2nd August 2018) - Sanders, T.; Elliott, J.; Norman, P.; Johnson, B.; Heller, S.
Abstract: Aims: To explore the experiences of young adults with regard to self‐management of Type 1 diabetes in the context of a structured education programme. Methods: Qualitative interviews and focus groups were conducted with young adults attending a structured education course promoting a flexible and self‐directed format. Participants attending the structured education courses were recruited using purposive sampling to acquire a broad mix of participants based on age and equal numbers of young men and women. Fifteen interviews were conducted 12 weeks after each course, whilst seven focus groups and observations of the course delivery were conducted at two course sites and were led by nurse/dietitian educators representing two different diabetes centres (paediatric and adult). The interview and focus group data were audio recorded and transcribed, coded, and analysed thematically to identify similarities and differences. Results: The analysis revealed three themes, 'we're in it together', 'tacit benefits' and 'transitions beyond the structured education programme'. The findings show that structured education programmes can facilitate reflective critical thinking and greater engagement with diabetes self‐management if they: a) foster maximal learning from fellow participants to decrease feelings of isolation, b) maximize engagement during the course by delivering the content in a flexible manner, and c) recognize the social and emotional needs of young adults. Conclusion: Structured education courses can result in improved critical thinking and engagement with diabetes self‐management by empowering young adults through a flexible and self‐directed learning style that encourages peer group discussion. What's new?: Young adults with Type 1 diabetes valued pragmatic knowledge for self‐management. A barrier to effective self‐management was the emotional burden of Type 1 diabetes. Peer group learning within the structured education programme promoted improved Type 1 diabetes self‐management. The course empowered young adults to engage with glucose control and facilitate an 'interface' with the diabetes clinic.